METHODOLOGY FOR ENHANCING STUDENTS’ MEDIA COMPETENCE THROUGH THE USE OF PODCASTS AND VLOGS - Tog’ayeva Muattar Bahodir qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation: In the digital era, media competence has become a fundamental component of students’ educational development, particularly in language learning contexts. This article explores methodological approaches to enhancing students’ media competence through the integration of podcasts and vlogs in the educational process. The study examines how these multimedia tools contribute to the development of critical thinking, communication skills, digital literacy, and content creation abilities. A mixed-method approach was used, including experimental teaching, observation, and assessment of students’ performance. The findings demonstrate that the use of podcasts and vlogs significantly improves students’ ability to analyze, interpret, and create media content. The article concludes with recommendations for educators on effectively integrating these tools into teaching practice.